Numerical analysis of the hydration of calcium oxide in a fixed bed reactor based on lab-scale experiments. (1st March 2020) - Risthaus, Kai; Bürger, Inga; Linder, Marc; Schmidt, Matthias
Highlights: First numerical study on the hydration of calcium hydroxide at 8.7–470 kPa. Validation of model for indirectly heated fixed bed reactor with experimental data. Thermal losses have major influence at pressure induced hydration reactions. Indirectly heated fixed beds are not limited by reaction kinetics at high pressure. Reaction kinetics become limiting for low pressures and relevant discharge power. Abstract: Thermochemical energy storage is gaining popularity as one possibility to integrate renewable energies into existing energy systems by providing large energy storage capacities at low costs. Systems based on the reversible reaction of calcium oxide and steam forming calcium hydroxide, are especially promising as the storage material is cheap, abundantly available, and non-toxic. Potential applications are the storage of industrial process heat, concentrated solar power, or novel power to heat concepts. Reactor design is increasingly accompanied by simulations. However, for indirectly heated fixed bed reactors, there currently exist only simulation models that are validated at 200 kPa. Therefore, a model coupling heat and mass transfer as well as the chemical reaction is set up and validated with recently published experimental data for an indirectly heated fixed bed with an operating range between 8.7 and 470 kPa. The simulation reveals that in this design with a thin reactive layer mass transfer is not limiting, while thermal losses have a significant influence and thus have to be accounted for in the model. Furthermore, at steam pressures above 200 kPa the reaction kinetics is not limiting and simplified kinetic models describe the reactor reasonably well. Whereas for lower pressures (below 50 kPa), the reaction kinetics becomes limiting and none of the analyzed kinetic models predict the reaction rate exactly. We conclude that the reaction kinetics at low steam pressures (8.7–50 kPa) is very sensitive towards pressure and temperature. The results can assist the design and upscaling of reactors for technical applications and show the necessity for further studies at low pressures.